Core Hairpin Structure of SpCas9 sgRNA Functions in a Sequence- and Spatial Conformation–Dependent Manner. (February 2021) - Jiang, Mingjun; Ye, Yanzhen; Li, Juan
The clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 system is a widely used genome-editing tool with great clinical potential. However, its application is limited because of low editing efficiency of some target sequences and off-target effects. As this system contains only the Cas9 protein and a single-guide RNA (sgRNA; engineered from crRNA and tracrRNA), the structure and function of these components should be studied in detail to address the current clinical needs. Consequently, we investigated the structural and sequence features of the core hairpin (the first stem loop of sgRNA) of SpCas9 sgRNA. We showed that the core hairpin structure of sgRNA is essential for SpCas9/sgRNA-mediated DNA cleavage and that the internal loop structure in the core hairpin plays a vital role in target DNA cleavage. We observed that the root stem structure within the core hairpin preferentially forms Watson-Crick base pairs and should be of a specific length to maintain an appropriate spatial conformation for Cas9 binding. However, the length of the leaf stem structure of the core hairpin is flexible, having a variable nucleotide composition. Furthermore, extension of the leaf stem structure enhances the DNA cleavage activity of the Cas9/sgRNA complex, and this could be used to enhance the efficiency of gene editing. These observations provide insight into the sgRNA/Cas9 interaction, indicating that sgRNA modification could be a strategy for improved DNA editing efficiency, and optimized sgRNA can be further used for genome-wide functional screening and clinical application.